Ultraviolet spectral behavior of UX Ari with periodic flaring activity - Sanad, M. R.; Zead, I.; Abdel-Sabour, M. A. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We present International Ultraviolet Explorer (IUE) observations of the luminous, noneclipsing, double lined spectroscopic binary system UX Ari over the period 1978-1996. Three spectra showing modulations in line fluxes at different times are presented. The ultraviolet spectra reveal emission lines originating in the chromosphere and transition region of the primary star. UX Ari has a periodic flaring activity in different wavelength bands each 7-9 years. The reddening of UX Ari determined from 2200 Å absorption feature to be E(B - V) = 0.14 ± 0.02. The calculated fluxes of CII 1335 Å , CIV 1550 Å & HeII 1640 Å emission lines showed a correlation with the orbital phase. The results confirmed that magnetic activity is the source and reason for emission lines and their changes. We determined the mass loss rate to be  M 6 10 yr-1, the temperature of the emitting region is 104 K ± 220 K, and the ultraviolet luminosity is 8 1029 erg s-1. The results agree with the inhomogeneous gyro-synchrotron model. редставлены результаты наблюдений IUE незатменной спектроскопической двойной системы с удвоенными линиями UX Ari за период 1978-1996гг. Представлены три спектра, показывающих модуляцию потоков в линиях в разное время. В ультрафиолетовых спектрах видны эмиссионные линии, происходящие из хромосферы и переходной области первичной звезды. Звезда показывает периодическую вспышечную активность в различных диапазонах длин волн каждые 7-9 лет. Покраснение UX Ari, определенное по абсорбционной характеристике 2200 Е , составило E(B - V) = 0.14 ± 0.02. Расчетные потоки эмиссионных линий CII 1335 Е , CIV 1550 Е и HeII 1640 Е показали корреляцию с орбитальной фазой. Результаты подтвердили, что магнитная активность является источником и причиной эмиссионных линий и их изменений. Мы определили скорость потери массы 1 10 6 млн/год, температуру излучающей области - 1 104 220 К, и ультрафиолетовую светимость - 8 1029 эрг с-1. Результаты согласуются с моделью неоднородного гиросинхротрона.
Keywords: Звезды